Strategic Approaches of Bandar Lampung's Election Supervisory Body in Oversight of the 2024 Election Campaigns - Isti Arini; Yudha, Gesit (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
The Election Supervisory Body (Bawaslu) holds a central mandate to oversee and address election violations, including monitoring vote counting, campaign finances, campaign materials such as banners, and preventing black campaigns and money politics. Bawaslu's supervision is guided by PERBAWASLU No. 11 BN 2023/No. 844 on the oversight of general election campaigns. However, there are frequent violations by political parties and legislative candidates, including the involvement of minors in campaigns, the installation of billboards that disrupt public order, and the use of campaign materials exceeding regulated dimensions. This study aims to examine the strategies employed by the Bandar Lampung City Election Supervisory Body (Bawaslu) in supervising the 2024 election campaigns and to identify the challenges encountered during this process. The research adopts a field-based approach with a descriptive-analytical method. The findings reveal that Bawaslu Bandar Lampung City employs several strategies, including: socialization and communication efforts, supervision of campaign materials, and monitoring indications of money politics. However, the institution faces significant obstacles, such as the anonymity of black campaign perpetrators, intimidation experienced by whistleblowers, and limitations in addressing campaign violations effectively. Although Bawaslu lacks full authority in legal enforcement, it remains committed to ensuring electoral integrity and fairness. This commitment underscores the importance of community involvement in fostering a clean and democratic electoral process.